Cretaceous small scavengers: feeding traces in tetrapod bones from Patagonia, Argentina. - Silvina de Valais; Sebastián Apesteguía; Alberto C Garrido (PLoS ONE, 2012)
Ecological relationships among fossil vertebrate groups are interpreted based on evidence of modification features and paleopathologies on fossil bones. Here we describe an ichnological assemblage composed of trace fossils on reptile bones, mainly sphenodontids, crocodyliforms and maniraptoran theropods. They all come from La Buitrera, an early Late Cretaceous locality in the Candeleros Formation of northwestern Patagonia, Argentina. This locality is significant because of the abundance of small to medium-sized vertebrates. The abundant ichnological record includes traces on bones, most of them attributable to tetrapods. These latter traces include tooth marks that provde evidence of feeding activities made during the sub-aerial exposure of tetrapod carcasses. Other traces are attributable to arthropods or roots. The totality of evidence provides an uncommon insight into paleoecological aspects of a Late Cretaceous southern ecosystem.